Empowerment Model for the Poor Communities in Urban Areas: A Study on Low-Income Households in Makassar - Faisal, Muhammad (Society, 2020)
Efforts to empower the poor communities in urban areas are still very urgent at this time. Although the number of poor communities in urban areas is decreasing, the rate is not significant. Empowerment needs to place poor urban as the main actors and the government as facilitators and motivators. This research aims to provide a scientific description of the causes of poverty and the empowerment model for the poor urban in Makassar city, South Sulawesi Province, Indonesia. The research method used is qualitative with a narrative strategy. The research participantss were as many as five low-income households in an urban area. The data collection technique used in-depth interviews with participants. Field observations were also made related to participants’ social life and literature studies to strengthen the interview and observation data. Data analysis takes three ways: data reduction, data display, and verification/conclusion drawing. The result showed three factors that cause urban poverty: natural, cultural, and structural. The empowerment model was implemented by understanding the problems encountered, developing problem-solving strategies, understanding the importance of making planned changes, and strengthening the urban poor’s capacity.